2019
DOI: 10.2134/cftm2018.07.0054
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Creeping Bentgrass Cultivar Germinability as Influenced by Cold Temperatures

Abstract: Core Ideas Golf course superintendents often overseed winter‐damaged areas with creeping bentgrass in the early spring when temperatures are not ideal for rapid germination. Typical spring temperatures in the upper Midwest were used to define treatments in a controlled environment study to determine general germination response from early April to late May. Response was measured across 21 cultivars to find those with superior germinability under suboptimal conditions. The study found that creeping bentgrass d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 21 publications
3
14
0
Order By: Relevance
“…No velvet bentgrass cultivar was ever observed to be in the top statistical performance group, along with 'Declaration' and 'L-93' creeping bentgrass and 'Tiger II' colonial bentgrass (Table 3). Heineck et al (2018) found 'Declaration' creeping bentgrass to have among the best seed germination rates for early spring laboratory test temperatures (mid-April) in their simulation test temperature of 7.0°C. Our field study indicated that 'Declaration' was a poor performer, requiring higher soil temperatures to achieve 90% grass cover during soil warming in early spring along with the lowest grass cover per day (4.5%/ d) and the lowest grass cover per°C (28.6%/°C) ( Table 2).…”
Section: Source Of Variationmentioning
confidence: 99%
See 3 more Smart Citations
“…No velvet bentgrass cultivar was ever observed to be in the top statistical performance group, along with 'Declaration' and 'L-93' creeping bentgrass and 'Tiger II' colonial bentgrass (Table 3). Heineck et al (2018) found 'Declaration' creeping bentgrass to have among the best seed germination rates for early spring laboratory test temperatures (mid-April) in their simulation test temperature of 7.0°C. Our field study indicated that 'Declaration' was a poor performer, requiring higher soil temperatures to achieve 90% grass cover during soil warming in early spring along with the lowest grass cover per day (4.5%/ d) and the lowest grass cover per°C (28.6%/°C) ( Table 2).…”
Section: Source Of Variationmentioning
confidence: 99%
“…Alternatively, 'Memorial' creeping bentgrass in our field study performed well in terms of grass cover (Table 3), higher grass cover per day, and higher grass cover per°C (Table 2). In laboratory simulation tests Heineck et al (2018) concluded 'Memorial' should not be recommended for planting in early spring because of poor germination characteristics at 7.0°C. These results underscore the need to validate, in the field, simulation test temperatures conducted in the laboratory, as suggested by the work of Hardegree and Van Vactor (2000) because of the numerous biological, chemical, and physiological factors affecting establishment in the field (Egli and TeKrony, 1996;Hegarty, 1973;Weaich et al, 1996).…”
Section: Source Of Variationmentioning
confidence: 99%
See 2 more Smart Citations
“…Heineck et al. (2019) evaluated the germination of 21 creeping bentgrass cultivars under four day–night temperature regimes of 45:35, 55:35, 60:40, and 70:50 °F, representing historical temperature data for potential seeding dates in the upper Midwest and determined that germination rates increased as temperatures increased. The authors also found that temperatures below 45 °F were too low for creeping bentgrass seed germination.…”
Section: Introductionmentioning
confidence: 99%